HYGIENIC EFFECT OF ENVIRONMENTAL FACTORS ON CHILDREN WITH ALLERGODERMATITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Allergodermatitis is a condition associated with inflammation of the skin and allergic reactions. It is a common problem in children and is often associated with food, textiles, chemicals, and environmental factors. Limiting children's contact with the outside environment, such as spending less time outdoors during pollen season, can help reduce allergic reactions. It is also important to encourage children not to go outside on days when air pollution is high. In this article we will talk about the hygienic effect of environmental factors on children with allergic dermatitis.